Identification of a Novel Nonsense Mutation in PLA2G6 and Prenatal Diagnosis in a Chinese Family With Infantile Neuroaxonal Dystrophy - Zou, Yongyi; Luo, Haiyan; Yuan, Huizhen; Xie, Kang; Yang, Yan; Huang, Shuhui; Yang, Bicheng; Liu, Yanqiu (Frontiers in Neurology, 2022)
Background and purpose Infantile neuroaxonal dystrophy (INAD) is a rare hereditary autosomal recessive neurodegenerative disorder caused by PLA2G6 mutations. Individuals affected with INAD are characterized by rapid progressive psychomotor deterioration, neuroregression, and hypotonia followed by generalized spasticity, optic atrophy, and dementia. In this case, we aimed to identify the underlying causative genetic factors of a Chinese family with two siblings who presented with walking difficulty and inability to speak. We provided prenatal diagnosis for the family and information for the prevention of this genetic disease. Methods Retrospective clinical information and magnetic resonance imaging (MRI) findings of the proband were collected. Trio-whole exome sequencing (WES) including the proband and his parents was performed to explore the genetic causes, while Sanger sequencing was subsequently used to validate the variants identified by Trio-WES in the pedigree. Furthermore, prenatal molecular genetic diagnosis was carried out through amniocentesis to investigate the status of pathogenic mutations in the fetus by Sanger sequencing at an appropriate gestational age. Results The two siblings were both clinically diagnosed with rapid regression in psychomotor development milestones. Brain MRI showed typical bilateral and symmetrical T2/FLAIR hyperintense signal changes in periventricular areas, indicating periventricular leukomalacia and myelin sheath dysplasia. Trio-WES revealed two heterozygous variants in PlA2G6 associated with clinical manifestations in the proband: a novel maternal inherited variant c.217C>T (p.Gln73*) and a previously reported paternal inherited recurrent pathogenic variant c.1894C>T (p.Arg632Trp). These two heterozygous mutations were also detected in the younger brother who had similar clinical features as the proband. The two variants that were identified were considered as the causative mutations for INAD in this family. Prenatal diagnosis suggested compound heterozygous mutations of c.217C>T and c.1894C>T in the fetus, indicating a high risk of INAD. Conclusion We identified a novel pathogenic mutation that broadens the mutation spectrum of PLA2G6 and will provide clues for molecular diagnosis of INAD. Furthermore, our study has helped to elucidate the causative genetic factors of this Chinese family with INAD effectively and efficiently by using the emerging Trio-WES strategy and providing precise genetic counseling for this family.